Health and Educational Inequalities among the Third Gender Community in Lahore, Pakistan: Inequalities in Health and Education for the Third Gender - Humayun, Ayesha; Hassan, Muhammad; Ashfaq, Hira; Haider, Zulqarnain; Naeem, Nauman; Mubashar Munir (Journal of University College of Medicine and Dentistry, 2025)
Objective: The third gender community, commonly referred to as the ‘hijra’ community and including transgender, intersex, and eunuch individuals, faces widespread societal discrimination, leading to marginalization and reduced opportunities for social and economic participation. This study aims to explore the educational and healthcare challenges faced by this community, as perceived by its members, to gain deeper insight into the complexities of their lived experiences. Methodology: This qualitative study conducted in-depth interviews with ten hijra individuals from three areas in Lahore, Pakistan. Data saturation was reached after eight interviews. Verbal consent was obtained with a transgender "Guru" as a witness. Transcriptions were coded by two researchers. Seven themes were identified: early childhood educational experiences, peer attitudes, educational costs, family attitudes, teacher behavior, discriminatory healthcare, and the attitudes of doctors and paramedical staff. Thematic analysis was conducted manually. Results: The study revealed that the hijra community faces minimal discrimination during early childhood education, but experiences significant bullying, harassment, and social exclusion in later school years, particularly from male peers and some teachers. Financial constraints often hinder their educational pursuits, with some parents being supportive while others are hostile. Healthcare discrimination is prevalent, with many reporting neglect and derogatory treatment from both public healthcare providers and paramedical staff, though private healthcare services offer better experiences for those who can afford them. These barriers underscore the systemic challenges faced by the hijra population in accessing education and healthcare. Conclusion: The third gender community faces significant barriers in accessing education and healthcare, depriving them of basic human rights. Urgent policy reforms promoting equity, inclusivity, and community sensitization are needed to end their social neglect. Keywords: Third gender, Hijra, Health, Discrimination, intersex, Eunuch